Effect of a previous sprint on the parameters of the work-time to exhaustion relationship in high intensity cycling - Heubert, R. A. P.; Billat, V. L.; Chassaing, P.; Bocquet, V.; Morton, R. H.; Koralsztein, J. P.; Di Prampero, P. E. (International Journal of Sports Medicine, 2005)
The relationships between both metabolic (E) and mechanical (W) energy expended and exhaustion time (te), was determined for 11 well-trained subjects during constant load cycloergometric exercises at 95, 100, 110, 115 % maximal aerobic power performed both from rest and, without interruption, after an all-out sprint of 7 s. These relationships were well described by straight lines: y = a + bte, where b was taken as the critical power (metabolic and mechanical) that can be sustained for long periods of time. b was unaffected by the exercise conditions and amounted to 82 - 94 % of maximal aerobic metabolic and mechanical power. The constant a was taken as the anaerobic stores capacity in excess of the O2 deficit. When the test was preceded by the sprint, a (metabolic and mechanical) was reduced to about 60 - 70 % of control values. This reduction was essentially equal to the corresponding E and W output during the sprint. These data support the view that the slope of linear regressions of E and W on te is indeed a measure of the critical power, whereas the y intercept of these same regressions is a measure of the anaerobic capacity.